Copper-Catalyzed Cyclization/Oxidation/Aromatization Cascade: Efficient Synthesis of Trifluoromethylated Pyrrolo[2,1-a]isoquinolines - Tao, Lili; Xu, Zhiliang; Han, Jing; Deng, Hongmei; Shao, Min; Chen, Jie; Zhang, Hui; Cao, Weiguo (Synthesis, 2016)
An efficient copper-catalyzed synthesis of 3-(trifluoromethyl)pyrrolo[2,1-a]isoquinolines was achieved through a sequential one-pot two-step three-component reaction of a substituted isoquinoline, a terminal aryne, and methyl 4,4,4-trifluorobut-2-ynoate, with air as an oxygen source. This oxidative cyclization proceeds through an initial copper(I)-catalyzed C–H alkynylation to give alkynyl-1,2-dihydroisoquinolines that subsequently undergo a copper(II)-assisted intramolecular cyclization under mild conditions to give the desired products in moderate to excellent yields.
Keywords: trifluoromethylation; isoquinolines; copper catalysis; multicomponent reaction; cascade reaction; C–H functionalization